Promising Therapy Candidates for Liver Fibrosis - Wang, Ping; Koyama, Yukinori; Liu, Xiao; Xu, Jun; Ma, Hsiao-Yen; Liang, Shuang; Kim, In H.; Brenner, David A.; Kisseleva, Tatiana (Frontiers in Physiology, 2016)
Liver fibrosis is a wound-healing process in response to repeated and chronic injury to hepatocytes and/or cholangiocytes. Ongoing hepatocyte apoptosis or necrosis lead to increase in ROS production and decrease in antioxidant activity, which recruits inflammatory cells from the blood and activate hepatic stellate cells changing to myofibroblasts. Injury to cholangiocytes also recruits inflammatory cells to the liver and activates portal fibroblasts in the portal area, which release molecules to activate and amplify cholangiocytes. No matter what origin of myofibroblasts, either hepatic stellate cells or portal fibroblasts, they share similar characteristics, including being positive for -smooth muscle actin and sproducing extra cellular matrix. Based on the extensive pathogenesis knowledge of liver fibrosis, therapeutic strategies have been designed to target each step of this process, including hepatocyte apoptosis, cholangiocyte proliferation, inflammation, and activation of myofibroblasts to deposit extracellular matrix, yet the current therapies are still in early-phase clinical development. There is an urgent need to translate the molecular mechanism of liver fibrosis to effective and potent reagents or therapies in human.